Ethics in Evaluating a Sociotechnical Intervention With Socially Isolated Older Adults. (November 2015) - Waycott, Jenny; Morgans, Amee; Pedell, Sonja; Ozanne, Elizabeth; Vetere, Frank; Kulik, Lars; Davis, Hilary
The purpose of this article is to consider how ethical principles can inform the effective design and implementation of technology-based interventions that aim to promote the well-being of socially isolated older adults. We evaluated a new iPad application with small groups of older adults. In this article, we reflect on the ethical issues encountered at each stage of the research process. Drawing on the ethical principles of beneficence, research merit and integrity, justice, and respect, we identify key issues to consider in the future design and implementation of social isolation interventions that use new technologies. Key issues include (a) providing sufficient support to facilitate ongoing social interactions, (b) managing older adults' expectations, (c) providing encouragement without coercion, and (d) responding to individual needs. We conclude that it is important to report on ethical challenges incurred when evaluating social isolation interventions to inform future research in this important area.